2022
DOI: 10.1038/s41598-022-06789-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of continuous and rotational cropping practices on soil chemical properties and microbial communities during peanut cultivation

Abstract: Long-term monocultures have severely inhibited the cultivation of Chinese peanut (Arachis hypogaea L.). In this study, the effects of continuous cropping on soil chemical properties and microbial communities were investigated in peanut fields that had been in crop rotation for 10 years and in monoculture for 10 years. The results found that long-term monoculture increased the activities of available potassium, available phosphorus, available nitrogen, soil organic matter, urease, acid phosphatase and catalase;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 71 publications
3
29
1
Order By: Relevance
“…Changes in richness and evenness ultimately led to the changes in bacterial diversity. This result does not agree with previous studies on sweet potato [ 10 , 38 , 41 ], rice [ 42 ], cotton [ 43 ], Lycium barbarum [ 40 ], and peanut [ 35 ], where bacterial diversity increased or decreased monotonically with continuous cropping time. However, a higher bacterial richness and bacterial diversity were found over 30 years and 10 years cropping with the highest for 30 years cropping of maize [ 44 ].…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…Changes in richness and evenness ultimately led to the changes in bacterial diversity. This result does not agree with previous studies on sweet potato [ 10 , 38 , 41 ], rice [ 42 ], cotton [ 43 ], Lycium barbarum [ 40 ], and peanut [ 35 ], where bacterial diversity increased or decreased monotonically with continuous cropping time. However, a higher bacterial richness and bacterial diversity were found over 30 years and 10 years cropping with the highest for 30 years cropping of maize [ 44 ].…”
Section: Discussioncontrasting
confidence: 92%
“…To comprehensively understand the rhizospheric soil bacterial community structure of Yongfeng yam in different continuous cultivation years, the Illumina NovaSeq method was used. These results revealed that the bacterial richness increased with the extension of continuous cultivation years, which is consistent with previous finding with peanut [ 35 ], Andrographis paniculate [ 36 ], and Rehmannia glutinosa [ 37 ], but is contrary to findings regarding sweet potato [ 38 ], Panax notoginseng [ 39 ], and Lycium barbarum [ 40 ]. The results of bacterial diversity (Shannon index) decreased first, remained stable, then increased with long-term continuous cropping, indicating a decrease in bacterial diversity up to 15 years of continuous cropping and an increase in bacterial diversity after 20 years.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations